Omrežje občin - povezanost v Alpah - projekt, ki živi - Kovačič, Neda (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 1999)
The article represents the basic elements of "Municipality network - connection in the Alps". It was a pilot project in 1997. Kranjska Gora was also included in the project according to the sustainable development and Alpine landscape protection guidelines. The results were some concrete projects.
Keywords: Alpe; Alps; environmental protection; Gorenjska; občine; regije; regionalni razvoj; Slovenia; Slovenija; sonaravni razvoj; sustainable development; trajnostni razvoj; Upper Carniola; varstvo okolja